Feeding strategy and cannibalism of the Argentine hake Merluccius hubbsi - Ocampo Reinaldo, Matías (2011)
The diet composition and feeding strategy of the Argentine hake Merluccius hubbsi in the San Matías Gulf were analysed in order to use this information for the sustainable management of the fishery. Merluccius hubbsi behaved as an opportunistic predator. Small M. hubbsi consumed plank- tonic crustaceans, whereas medium and large fish ate numerous prey taxa with low frequency of occurrence and variable specific abundance. Intra- and intercohort cannibalism were detected in all size groups and were particularly significant in large M. hubbsi. Medium-sized M. hubbsi consumed small conspecifics and large-sized M. hubbsi consumed both small and medium M. hubbsi.These results indicate that the removal of large M. hubbsi by fishing may increase the risk of overfish- ing by two combined effects: a direct effect of recruitment-overfishing and an indirect effect of growth-overfishing through an enhanced cannibalism of medium M. hubbsi on small M. hubbsi. Intra- and intercohort cannibalism and other trophic relationships in the M. hubbsi should therefore be considered explicitly in stock assessment models.